An evaluation on the relationship between the learning fields “musical perception and acquainting” and “musical creativity” based on teaching program of 2006 primary education music classes of sixth grade level 2006 İlköğretim müzik dersi 6. sınıf öğretim programı içerisinde yer alan “müziksel algı ve bilgilenme” ile “müziksel yaratıcılık” öğrenme alanları arasındaki ilişkisel durumun değerlendirilmesi - Parasız, Gökalp; Aras, Tuncay (Journal of Human Sciences, 2014)
In this study, it was intended to focus on the success levels of “B. Musical Perception and Acquainting” learning field and of “C. Musical Creativity” learning field based on the teaching program of 2006 primary education music classes of sixth grade level and relationship between these two learning fields was evaluated. In this study the basic stages, the vision, the basic approach, and the structure of the teaching program of 2006 primary education music classes and the general aims, basic skills and valuation, teaching methods and techniques and learning-teaching period were examined. Source scanning related to these subjects was done. Outcomes and activities related to “B. Müziksel Algı ve Bilgilenme” and “C. Müziksel Yaratıcılık” learning fields in this study were analyzed by using observation method. Sample group of this study consisted of 6-A, 6-C, 6-E, 6-G classes in IMKB İnönü Primary School in Erzurum depended on Ministry of National Education. To analyze all data based on observation, frequency (f) percent (%) analysis method was used. Findings and comments part of the study included data that was acquired as a result of outcomes of two basic learning fields and in this part data were interpreted according to the findings. After collecting all data and evaluating the relationship between “B. Musical Perception and Acquainting” learning field and “C. Musical Creativity” learning field, to the results, it was acquired that these two learning fields had supportive and complementary to each other. According to the results of the study, when music class practices are structured considering the relationship between two basic learning fields, learning becomes easier and more comprehensible and by this way, learning continuity will be provided. Özet Bu araştırmada, 2006 İlköğretim müzik dersi 6.sınıf öğretim programında yer alan “B. Müziksel Algı ve Bilgilenme” ile “C. Müziksel Yaratıcılık” öğrenme alanlarının başarı düzeyleri ve bu iki öğrenme alanları arasındaki ilişkisel durum değerlendirilmiştir. Araştırmada, 2006 İlköğretim müzik dersi öğretim programın aşamaları, programın vizyonu, programın temel yaklaşımı, programın temel yapısı, genel amaçlar, temel beceriler ve değerler, öğretim yöntem ve teknikleri, öğrenme-öğretme süreci incelenmiş ve konuya ilişkin olarak kaynak taraması yapılmıştır. Araştırma içerisinde yer alan “B. Müziksel Algı ve Bilgilenme” ile “C. Müziksel Yaratıcılık” öğrenme alanlarına ait kazanımlar ve etkinlikler gözlem yöntemi ile incelenmiştir. Araştırmanın örneklemini; Erzurum İMKB İnönü ilköğretim okulunda bulunan 6-A, 6-C, 6-E, 6-G sınıfları oluşturmuş olup, gözlem yöntemi kullanılarak elde edilen veriler frekans(f) yüzde (%) analizine göre çözümlenmiştir. Araştırmanın bulgular ve yorumlar kısmında, iki temel öğrenme alanlarına ait kazanımlardan elde edilen bulgulara yer verilmiş ve bulgular ışığında veriler yorumlanmıştır. Araştırma sonucunda; “B. Müziksel Algı ve Bilgilenme” ile “C. Müziksel Yaratıcılık” öğrenme alanlarının arasındaki ilişkisel durum değerlendirilerek birbirlerini destekleyici ve tamamlayıcı yönlerinin olduğu sonucuna varılmıştır. Araştırmanın sonuçlarından yola çıkılarak; müzik dersi uygulamaları, iki temel öğrenme alanları arasındaki ilişkisel durum göz önünde bulundurularak yapılandırıldığında, öğrenme daha kolay ve daha anlaşılır bir şekilde gerçekleşecek, öğrenmenin sürekliliği de sağlanmış olacaktır.